KAJIAN YURIDIS DAMPAK TEKNOLOGI DIGITAL TERHADAP KEPASTIAN HUKUM DALAM TRANSAKSI BISNIS - Rahmat Giling; Pandri Zulfikar; Mahmuddin; Dany Wahyu; Nursalim (Berajah Journal, 2026)
The development of digital technology has brought about a fundamental transformation in the conduct of modern business transactions. The emergence of blockchain technology, smart contracts, electronic signatures and e-commerce platforms has changed the conventional paradigm of conducting transactions. However, this digital transformation poses significant challenges to legal certainty in business transactions, particularly in relation to legal validity, consumer protection, dispute resolution and jurisdiction. This study aims to analyse the impact of digital technology on legal certainty in business transactions from a legal perspective using a normative legal research method. The results of the study indicate that digital technology has a two-sided impact on legal certainty: on the one hand, it enhances the efficiency and transparency of transactions; on the other hand, it creates legal uncertainty due to regulations that have not yet been able to keep pace with technological developments. This study recommends the need to harmonise national regulations with international standards, as well as the establishment of a specific legal framework for digital transactions to ensure optimal legal certainty.